The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1007/s00592-020-01566-w
|View full text |Cite
|
Sign up to set email alerts
|

The difference between steroid diabetes mellitus and type 2 diabetes mellitus: a whole-body 18F-FDG PET/CT study

Abstract: Aims Steroid diabetes mellitus (SDM) is a metabolic syndrome caused by an increase in glucocorticoids, and its pathogenesis is unclear. 18F-FDG PET/CT can reflect the glucose metabolism of tissues and organs under living conditions. Here, PET/CT imaging of SDM and type 2 diabetes mellitus (T2DM) rats was used to visualize changes in glucose metabolism in the main glucose metabolizing organs and investigate the pathogenesis of SDM. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
(51 reference statements)
1
5
0
Order By: Relevance
“…For the patients in whom well-known causes of ESMU were excluded, the incidence of ESMU was 0.259% (23/8866 scans) overall, 0.230% (12/5211 scans) in men, and 0.301% (11/3655 scans) in women. Our study demonstrated that ESMU may be associated with steroid administration history in humans, which was also observed in an animal study using rats 2 . In addition, we found that the mean SUV max of the measured skeletal muscle tended to decrease with the increase in the number of days elapsed since the last steroid administration (Fig.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…For the patients in whom well-known causes of ESMU were excluded, the incidence of ESMU was 0.259% (23/8866 scans) overall, 0.230% (12/5211 scans) in men, and 0.301% (11/3655 scans) in women. Our study demonstrated that ESMU may be associated with steroid administration history in humans, which was also observed in an animal study using rats 2 . In addition, we found that the mean SUV max of the measured skeletal muscle tended to decrease with the increase in the number of days elapsed since the last steroid administration (Fig.…”
Section: Discussionsupporting
confidence: 85%
“…Our study demonstrated that ESMU may be associated with steroid administration history in humans, which was also observed in an animal study using rats. 2 In addition, we found that the mean SUV max of the measured skeletal muscle tended to decrease with the increase in the number of days elapsed since the last steroid administration (Fig. 3).…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations